Mercury and methylmercury in the Atlantic sector of the Southern Ocean. (April 2017) - Canário, João; Santos-Echeandia, Juan; Padeiro, Ana; Amaro, Eduardo; Strass, Volker; Klaas, Christine; Hoppema, Mario; Ossebaar, Sharyn; Koch, Boris P.; Laglera, Luis M.
Abstract: Oceans constitute one of the most important reservoirs for mercury. In order to provide a first insight into the concentrations of Hg species in the Atlantic sector of the Southern Ocean a sampling campaign was carried out south of the Polar Front. Water samples taken at discrete depths from the surface down to 300 m at six stations were analysed for total Hg (HgT), methylmercury (MeHg) and other interpretative parameters such as salinity, temperature, dissolved and particulate organic carbon, dissolved oxygen, chlorophyll and inorganic nutrients. Results showed a high spatial variability in the concentrations of HgT and MeHg. HgT (0.93±0.69 ng L −1 ) and MeHg (0.26±0.12 ng L −1 ) levels were similar or higher than those reported in previous works in high latitude studies. The highest values were found at a location (−53°, 10°E) south of the South Polar Front, an area of strong gradients caused by the mixing of different water masses. Vertical profiles showed a great variability even for those stations sampled at the same location or an area dominated by the same oceanographic features. A decrease of HgT and a consequent increase in MeHg with depth was observed in some sites, suggesting the occurrence of Hg-methylation process, while at other stations, a concurrent decrease or increase of both mercury species was observed. In spite of these differences, an overall positive correlation between HgT and MeHg was observed. Differences between vertical profiles of Hg species were attributed to favourable environmental conditions for Hg methylation. The highest proportion of MeHg (% of HgT) was observed in sites with low dissolved oxygen or highest estimated remineralization rates. The results obtained in this study show that the Hg distribution and speciation in the Atlantic sector of the SO is comparable (or in some sites higher) to the ones published for the other open ocean regions. However, the concentrations of MeHg in this area are more dependent on the environmental conditions than on the total concentration of Hg present in the water.